Formation Of Values as Psychological Immunity in Adolescent Children in The Conditions of Information Threat - Alievich, Ergashev Eminjon; Ergashevna, Yulchiboyeva Dilfuza (International Journal of Membrane Science and Technology, 2023)
In the article, in the formation of psychological immunity in adolescent children in the conditions of information threats, based on the requirements of the present time, the uniqueness of the formation of values in adolescent children and the conducted researches are analyzed and the priority values are defined.